Athletes' Motivation in Traditional Martial Arts Participation: A Descriptive Study of Pagar Nusa Pencak Silat - Dinata, Aria; Suwirman, Suwirman; Asnaldi, Arie; Sasmitha, Weny (International Martial Arts and Culture Journal, 2024)
Background and Aim. Traditional martial arts, including Pencak Silat, play a role in developing the physical, mental, and character of athletes. In the context of community-based training like Pencak Silat Pagar Nusa, athlete motivation is one factor influencing the sustainability of participation and the quality of training. This study aims to describe athletes' motivation in participating in Pencak Silat Pagar Nusa activities by examining intrinsic and extrinsic motivation.Method. This study employed a descriptive quantitative design. Participants were 20 Pagar Nusa Pencak Silat athletes from Rimbo Bujang District, Tebo Regency. Data were collected using a motivational questionnaire covering intrinsic and extrinsic motivational aspects, then analyzed descriptively using percentages to describe the athletes' motivation levels.Results. The results of the study indicate that athlete motivation is in the high category. Most athletes have excellent intrinsic and extrinsic motivation, with overall motivation levels predominantly in the highest category. These findings indicate that athlete involvement in Pagar Nusa Pencak Silat activities is supported by strong internal motivation and a conducive coaching environment.Conclusion. This study concludes that Pagar Nusa Pencak Silat athletes have very high levels of intrinsic and extrinsic motivation. These results underscore the importance of community-based traditional martial arts development in creating psychological conditions that support sustained athlete participation. The findings of this study can serve as a basis for coaches and trainers in designing more effective and sustainable development strategies.